High-rate cycle type high-voltage soft package lithium ion battery and preparation method thereof

By adopting a high-rate cycle design in lithium-ion batteries, combined with specific materials and process flows, the insufficient performance of lithium-ion batteries in high-temperature short circuit, discharge platform and volume-energy ratio is solved, and higher battery performance and A wider range of applications.

CN119181836APending Publication Date: 2024-12-24FENGFAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411163096.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have insufficient performance in high-temperature short circuit, discharge platform and volume-energy ratio, and cannot achieve the four performance improvements, which limits their widespread use.

Method used

Designed with high-speed cycling high-voltage soft-pack lithium-ion battery, including specific combinations of positive and negative electrode slurries, diaphragms and electrolytes, through optimizing materials and process flow, such as the positive electrode intermediate outlet method, ceramic coated diaphragms, rolls Core assembly and pressurized heating short circuit test improve the high temperature safety and chemical performance of the battery.

Benefits of technology

It achieves a higher discharge platform, a 1.5C-ratio charge and discharge cycle capacity retention rate, meets the performance of 55℃ high-temperature short circuit and volume-energy ratio of more than 550Wh/L, and expands the use range of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181836A_ABST
    Figure CN119181836A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a high-rate circulation type high-voltage soft package lithium ion battery and a preparation method thereof.The soft package lithium ion battery comprises a positive plate, a negative plate, a diaphragm, electrolyte and an aluminum plastic film; the high-rate circulating type high-voltage soft package lithium ion battery is obtained by improving the ratio of positive and negative electrode materials, preparing negative electrode slurry, preparing positive and negative electrode pieces, winding and assembling a roll core and performing subsequent production. The battery prepared by the invention can have a higher discharge platform, the capacity retention ratio of 1.5 C-rate charge and discharge-300 cycles is 80% or above, the performance of 55 DEG C high-temperature short circuit and the volume energy ratio of 600 Wh / L or above is met, and the application range of the lithium ion battery is effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-rate cycle type high-voltage soft-pack lithium ion battery and a preparation method thereof. Background Art

[0002] With the continuous advancement of technology, modern mobile devices are becoming more and more diverse, and as the main energy supply component of mobile devices (lithium-ion batteries), they are receiving more and more attention and attention from the public. The competition in the lithium-ion battery market is becoming increasingly fierce. In order to enhance their competitiveness, major manufacturers are constantly improving battery performance. High discharge platform, fast charge and discharge, and high volume energy ratio are the mainstream development trends of the subsequent industry.

[0003] However, the batteries in the industry currently generally have problems such as a low discharge platform, a charge and discharge cycle rate of only 0.5-1.0C, an inability to withstand a high temperature short circuit of 55°C, a volume energy ratio of around 500Wh / L, or only an improvement in one of the four items but an inability to achieve a breakthrough in all four performances, which has limited the wider use of batteries.

[0004] Therefore, it is an urgent problem for technicians in this field to provide a high-rate cycle-type high-voltage soft-pack lithium-ion battery and a preparation method thereof. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-rate cycle high-voltage soft-pack lithium-ion battery and a preparation method thereof. The battery prepared by the present invention can have a higher discharge platform, a capacity retention rate of more than 80% for 1.5C rate charge and discharge-300 cycles, meet the performance of 55°C high-temperature short circuit, and a volume energy ratio of more than 600Wh / L, effectively broadening the scope of use of lithium-ion batteries.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A high-rate cycle type high-voltage soft-pack lithium-ion battery, the soft-pack lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum-plastic film;

[0008] Wherein, the positive electrode sheet comprises a positive electrode slurry and a positive electrode current collector;

[0009] The negative electrode sheet comprises a negative electrode slurry and a positive electrode current collector;

[0010] The diaphragm is a three-layer diaphragm including a PE base film, a ceramic coating and a ceramic adhesive coating;

[0011] The electrolyte additive includes at least one of DTD, FEC and HTCN;

[0012] The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP.

[0013] Preferably, the solvent of the positive electrode slurry is NMP, the solid material content of the positive electrode slurry is 65-70% by mass, and the viscosity of the positive electrode slurry is 7500-9500 mpa.s;

[0014] The solid material comprises the following raw materials in percentage by mass: 94-97% of five-series or six-series high-voltage ternary, 0.5-1.5% of conductive agent, 1.0-2.0% of conductive paste and 1.5-2.5% of binder;

[0015] The positive electrode current collector is an aluminum foil with a thickness of 10-15 um.

[0016] Preferably, the solvent of the negative electrode slurry is water and NMP, the mass percentage of the solid material content of the negative electrode slurry is 40-50%, and the viscosity of the negative electrode slurry is 2000-4000 mpa.s;

[0017] The solid material comprises the following raw materials in percentage by weight: 77-82% of graphite, 13.6-17.2% of silicon oxide, 0.8-1.2% of conductive agent, 0.05-0.1% of conductive paste, 1.35-1.5% of CMC and 2.2-3.0% of suspending agent; the amount of NMP added is 1-4% of the weight of the solid material;

[0018] The negative electrode current collector is a copper foil with a thickness of 5-8 um.

[0019] Preferably, the thickness of the diaphragm is 12-15um, wherein the thickness of the PE base film is 6-10um, the thickness of the ceramic coating is 1-4um, and the thickness of the ceramic glue coating is 1-3um;

[0020] The mass percentage of the additive is 1.5%;

[0021] The thickness of the aluminum-plastic film is 0.088-0.113 mm.

[0022] According to the above-mentioned method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery, the following specific steps are included:

[0023] (1) Preparation of positive electrode slurry and positive electrode sheet;

[0024] (2) Preparation of negative electrode slurry and negative electrode sheet;

[0025] (3) The materials are sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle-type high-voltage soft-pack lithium-ion battery.

[0026] Preferably, the preparation of the positive electrode slurry in step (1) specifically includes the following steps:

[0027] (1-1) Weighing raw materials: weigh the raw materials of the positive electrode slurry according to the mass percentages described in claim 1 or 2;

[0028] (1-2) Dry powder mixing: Add five-series or six-series high-voltage ternary, conductive agent and binder in sequence and stir to obtain mixed dry powder;

[0029] (1-3) mud-like stirring: adding a portion of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture;

[0030] (1-4) After adding the conductive slurry to the muddy mixture and stirring evenly, the remaining NMP is added to adjust the viscosity to 7500-9500 mPa.s to obtain the positive electrode slurry.

[0031] Preferably, the positive electrode sheet in step (1) is prepared by means of a positive electrode middle tab, and the tab is affixed with high temperature resistant masking tape.

[0032] The positive electrode sheet preparation method of the present invention, on the one hand, blocks the diaphragm failure problem caused by the thermal effect of the current at the positive electrode tab when the battery is subjected to a high-temperature short circuit, thereby improving the high-temperature safety performance of the battery; on the other hand, the high liquid absorption property of the masking tape itself is used to increase the liquid retention effect of the battery, thereby improving the various chemical properties of the battery.

[0033] Preferably, the preparation of the negative electrode slurry in step (2) specifically includes the following steps:

[0034] (2-1) Weighing raw materials: weighing raw materials for negative electrode slurry according to the mass percentages described in claim 1 or 3;

[0035] (2-2) Preparation of glue solution: the CMC and the water are mixed and then glued to obtain glue solution, wherein the viscosity of the glue solution is 2000-4000 mPa.s;

[0036] (2-3) Preparation of graphite pre-slurry: After dry powder mixing of the graphite and part of the conductive agent, adding part of the glue solution for primary infiltration and stirring; then adding part of the conductive slurry for secondary infiltration and stirring; finally, adding water for viscosity adjustment to 6000-6500 mPa.s to obtain graphite pre-slurry;

[0037] (2-4) Preparation of silicon oxide pre-slurry: After dry powder mixing of the silicon oxide and the remaining conductive agent, a portion of the glue solution is added for primary wetting and stirring; then the remaining conductive paste is added for secondary wetting and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain silicon oxide pre-slurry;

[0038] (2-5) Liquid fusion: The graphite pre-slurry and the silicon oxide pre-slurry are mixed and stirred for liquid dissolution. After completion, the remaining glue solution is added for dilute glue stirring, and then the water is added for viscosity adjustment to 2000-4000 mPa.s. Finally, the suspending agent is added in sequence for suspension stirring and NMP is added for inversion degassing to obtain the negative electrode slurry.

[0039] The negative electrode slurry preparation of the present invention is divided into four steps. First, CMC is prepared into a glue solution, so that the powdered CMC is used in the subsequent slurry preparation in liquid form, which increases the dispersion effect of CMC and enhances the stability of the slurry.

[0040] Secondly, in the preparation process of graphite pre-slurry and silicon oxide pre-slurry, the corresponding materials are added in different slurry states of solid-slightly wet-mud-thin mud, which not only increases the dispersion uniformity of graphite or silicon oxide and conductive agent, but also partially introduces the binder into the mixed system in the slightly wet state of the slurry, which enhances the dispersion effect of the binder and the bonding effect of the binder; and after the first infiltration and stirring, a certain amount of conductive slurry is added to the slightly wet mixture for further infiltration and stirring, which makes the graphite or silicon oxide, conductive agent and binder more evenly dispersed on the one hand, and on the other hand, the stirring resistance in the slightly wet state of the slurry is small but there is a certain friction resistance. At this time, the addition of conductive slurry will not cause the conductive slurry to be unable to be fully dispersed or the shear force is too large to break the carbon tubes in the conductive slurry and fail, and will not cause the conductive slurry to agglomerate and be unable to be uniformly planned due to too small friction resistance; after the second infiltration and stirring, the slurry viscosity is adjusted by adding deionization, so that the slurry viscosity is between 6000-6500mpa.s, which is convenient for subsequent steps;

[0041] In addition, the present invention avoids the drawback that the two main materials of the negative electrode (silicon oxide and graphite) account for a large proportion and have a large difference in particle size distribution and cannot be fully fused and dispersed by fusing and stirring the graphite pre-slurry and silicon oxide pre-slurry prepared in the early stage in the liquid state. In addition, in the early stage of the pre-slurry preparation process, the viscosity of the two pre-slurries is adjusted to a similar viscosity state, so that the two pre-slurries are more smoothly fused in this step, avoiding fusion bubbles caused by viscosity differences, and making the dispersion of various materials more uniform.

[0042] At the same time, by further adding glue to the slurry after the liquid-dissolving stirring and stirring it, on the one hand, the full dispersion of the components in the slurry is further enhanced, and on the other hand, the adhesive effect of the slurry is increased, so that the interaction between the components in the slurry is enhanced and the slurry is more stable; finally, by adding suspending agent and NMP to the slurry after the viscosity is adjusted to meet the requirements and stirring it, the stability and producibility of the slurry are enhanced, laying the foundation for the convenience of subsequent slurry production and the excellent electrochemical performance of the battery.

[0043] Preferably, in step (2-3), the amount of the conductive agent added is 4 / 5-5 / 6 of the total amount, the amount of the glue added is 2 / 5-5 / 12 of the total amount, and the amount of the conductive paste added is 4 / 5-5 / 6 of the total amount;

[0044] In step (2-4), the amount of the conductive agent added is 1 / 6-1 / 5 of the total amount, the amount of the glue added is 1 / 12-1 / 10 of the total amount, and the amount of the conductive paste added is 1 / 6-1 / 5 of the total amount.

[0045] Preferably, the winding core assembly in step (3) is wound using a ceramic rubber diaphragm, and after the winding is completed, the winding core is subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production;

[0046] The specific parameters of the pressurized and heated short-circuit test and the pressurized low-temperature rapid cooling shaping production are as follows:

[0047] The temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 1-2 minutes, and the surface pressure is 5±0.5kgf / cm 2 ;

[0048] The temperature of the pressurized low-temperature rapid cooling setting is 10±3°C, the time is 1-2min, and the surface pressure is 6±0.5kgf / cm 2 .

[0049] The purpose of the core assembly operation in the present invention is to melt the ceramic glue in the diaphragm by high-temperature heating, further bond the diaphragm and the electrode piece by pressurizing, and then achieve short-time solidification of the ceramic glue by rapid cooling treatment, so as to avoid the loose adhesion between the electrode piece and the diaphragm caused by the rebound of the core after the pressure disappears; on the one hand, the method of the present invention reduces the poor packaging caused by the rebound of the core space in the subsequent top and side sealing process, and on the other hand, increases the adhesion between the electrode piece and the diaphragm, which inhibits the electrochemical rebound in the subsequent formation and capacity division process of the battery, and then plays a positive role in promoting the appearance and various performances of the battery.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The soft-pack lithium-ion battery prepared by the raw materials and methods of the present invention can achieve a higher discharge platform, a capacity retention rate of more than 80% after 1.5C rate charge and discharge for 300 cycles, meet the requirements of 55°C high-temperature short circuit, and a volume energy ratio of more than 550Wh / L, which effectively broadens the scope of use of lithium-ion batteries;

[0052] (2) The present invention adopts a specific slurry mixing method to make the graphite, silicon oxide, conductive agent and suspending agent of different particle sizes dispersed more evenly, so that the slurry stability is stronger and the production performance and finished product performance are improved simultaneously;

[0053] (3) The present invention achieves the purpose of improving the safety performance of the battery, improving the battery's liquid retention capacity, and improving various chemical properties of the battery by adopting a method of providing a tab in the middle of the positive electrode and attaching a high-temperature resistant masking tape to the tab of the positive electrode;

[0054] (4) The present invention uses ceramic glue diaphragm winding during the core assembly process and adopts pressurized and heated short-circuit testing and pressurized low-temperature rapid cooling to shape the core, which effectively suppresses the battery arching problem caused by the large rebound of the negative electrode silicon oxide material, thereby achieving a simultaneous improvement in product appearance and various performances. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0056] Figure 1 Schematic diagram of the structure of the positive electrode sheet of Examples 1 and 2;

[0057] Figure 2 Schematic diagram of the structure of the positive electrode sheet of Comparative Example 2;

[0058] Figure 3 A comparison chart of discharge curves of batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries;

[0059] Figure 4 Cycle comparison curves of batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries;

[0060] Figure 5 Rate comparison curves of the batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries. DETAILED DESCRIPTION

[0061] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] A high-rate cycle high-voltage soft-pack lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum-plastic film;

[0064] Among them, the positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the current collector. The positive electrode slurry solvent is NMP, the solid material content is 69%, the slurry viscosity is 8500mpa.s, and the solid material contains 96.5% of the six-series high-voltage ternary (Jinfuli: 06T7), 0.8% of the conductive agent LI-20, 1.2% of the conductive slurry (Haiwei Jiaye O2H017) and 1.5% of the binder PVDF; the positive electrode current collector is 12um aluminum foil;

[0065] The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the current collector. The negative electrode slurry solvent is deionized water and NMP (the amount of NMP added is 1% of the mass of the solid material), the solid material content is 47%, the slurry viscosity is 2500mpa.s, and the solid material contains 80% graphite (Inner Mongolia Sanxin S1), 15% silicon oxide (Lianchuang: LCL14-1), 1.0% conductive agent LI-20, 0.1% conductive slurry (Haiwei Jiaye O2H017), 1.4% CMC and 2.5% suspending agent SBR; the negative electrode current collector is 6um copper foil;

[0066] The diaphragm is a three-layer diaphragm with a thickness of 15um, including a PE base film, a ceramic coating and a ceramic adhesive coating. The thickness of the PE base film is 9um, the thickness of the ceramic coating is 3um, and the thickness of the ceramic adhesive coating is 3um. The ceramic and ceramic adhesive are applied in separate coating processes.

[0067] The electrolyte lithium salt concentration is 1.5 mol / L, the solvent ratio is EC:EMC:PC:PA:EA=25:15:10:35:15, and 1.5% DTD additive is added;

[0068] The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP and a thickness of 0.088mm;

[0069] The preparation method of the soft-pack lithium-ion battery comprises the following specific steps:

[0070] (1) Preparation of positive electrode slurry and positive electrode sheet. The positive electrode sheet is prepared by using the positive electrode middle tab method and affixing high temperature resistant masking tape to the positive electrode tab. The specific structure is as shown in the attached figure. Figure 1 As shown;

[0071] (2) Preparation of negative electrode slurry and negative electrode sheet;

[0072] (3) The material is sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle high-voltage soft-pack lithium-ion battery, wherein a ceramic rubber diaphragm is used for winding during the core assembly, and after the winding is completed, the core needs to be subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production. The temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 1 min, and the surface pressure is 5±0.5kgf / cm 2 ; The temperature of pressurized low temperature rapid cooling is 10±3℃, the time is 1min, and the surface pressure is 6±0.5kgf / cm 2 , the actual set pressure calculation formula is as follows: set pressure = core width * core height - surface pressure;

[0073] in,

[0074] The preparation of the positive electrode slurry specifically includes the following steps:

[0075] (1-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the positive electrode slurry;

[0076] (1-2) Dry powder mixing: Add the raw materials in the order of main material five-series or six-series high-voltage ternary 50%, conductive agent LI-20 100%, PVDF 100% and the remaining main materials, and stir the dry powder for 30 minutes to obtain a mixed dry powder;

[0077] (1-3) mud-like stirring: adding 28% by weight of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture;

[0078] (1-4) High viscosity stirring: Add the obtained muddy mixture to the conductive slurry and stir evenly, then add the remaining NMP to adjust the viscosity. After the viscosity is adjusted to 8500 mPa.s, degassing is performed to obtain the positive electrode slurry. The specific stirring process is shown in Table 1;

[0079] Table 1. Cathode slurry stirring process parameters

[0080]

[0081] The preparation of negative electrode slurry specifically includes the following steps:

[0082] (2-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the negative electrode slurry;

[0083] (2-2) Preparation of glue solution: CMC and deionized water are added into a mixing barrel at a ratio of 1.4:98.6 and stirred. First, stir at a low speed for 5 minutes, change the speed after cleaning and stir for 10 minutes, clean again, and then stir at a high speed for 20 minutes. After the high-speed stirring, observe that the glue solution is transparent and clear, and there are no glue particles in the glue solution. If there are residual undissolved glue particles in the glue solution, the glue application time is extended by 30-60 minutes accordingly. After the glue solution is qualified, vacuum degassing is carried out for 10 minutes before discharging. The final glue solution viscosity is 2500mpa.s.

[0084] (2-3) Preparation of graphite pre-slurry: Graphite and 5 / 6 of the conductive agent were added to a mixing barrel for dry powder stirring; then, 5 / 12 of the glue solution was added and stirred for a first soaking; then, 5 / 6 of the conductive slurry was added for a second soaking and stirring; finally, deionized water was added for viscosity adjustment, and the final viscosity was 6320 mPa.s. The specific stirring process is shown in Table 2;

[0085] Table 2 Graphite pre-slurry stirring process parameters

[0086]

[0087] (2-4) Preparation of silicon oxide pre-slurry: Add silicon oxide and the remaining conductive agent into a slurry mixing barrel and stir the dry powder; then, add 1 / 12 of the glue solution and stir it once; then, add the remaining conductive slurry and stir it twice; finally, add deionized water to adjust the viscosity, and the final viscosity is 6270 mPa.s. The specific stirring process is shown in Table 3;

[0088] Table 3 Silica pre-slurry mixing process parameters

[0089]

[0090] (2-5) Liquid fusion: Add graphite pre-slurry and silica pre-slurry into a mixing barrel for liquid dissolution stirring; then, add the remaining glue solution and stir for dilute glue; then adjust the slurry viscosity by adding deionized water, and the final viscosity is 2500mPa.s; then, add the suspending agent SBR to the slurry after the viscosity adjustment is qualified and suspend and stir; finally, add NMP to the slurry after stirring and reverse degassing to obtain qualified negative electrode slurry. The specific stirring process is shown in Table 4;

[0091] Table 4 Silica pre-slurry mixing process parameters

[0092]

[0093] Example 2

[0094] A high-rate cycle high-voltage soft-pack lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum-plastic film;

[0095] Among them, the positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the current collector. The positive electrode slurry solvent is NMP, the solid material content is 72%, the slurry viscosity is 9200mpa.s, and the solid material contains 96% of six-series high-voltage ternary, 1.0% of conductive agent LI-20, 1.5% of conductive slurry and 1.5% of binder PVDF; the positive electrode current collector is 12um aluminum foil;

[0096] The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the current collector. The negative electrode slurry solvent is deionized water and NMP (the amount of NMP added is 4% of the mass of the solid material), the solid material content is 49%, the slurry viscosity is 2950mpa.s, and the solid material contains 78% graphite, 16.5% silicon oxide, 1.5% conductive agent LI-20, 0.05% conductive slurry, 1.45% CMC and 2.5% suspending agent SBR; the negative electrode current collector is 6um copper foil;

[0097] The diaphragm is a three-layer diaphragm with a thickness of 13um, including a PE base film, a ceramic coating and a ceramic adhesive coating. The thickness of the PE base film is 9um, the thickness of the ceramic coating is 2um, and the thickness of the ceramic adhesive coating is 2um. The ceramic and ceramic adhesive are applied in separate coating processes.

[0098] The electrolyte lithium salt concentration is 1.5 mol / L, the solvent ratio is EC:EMC:PC:PA:EA=25:15:10:35:15, and 1.5% DTD additive is added;

[0099] The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP and a thickness of 0.088mm;

[0100] The preparation method of the soft-pack lithium-ion battery comprises the following specific steps:

[0101] (1) Preparation of positive electrode slurry and positive electrode sheet. The positive electrode sheet is prepared by using the positive electrode middle tab method and affixing high temperature resistant masking tape to the positive electrode tab. The specific structure is as shown in the attached figure. Figure 1 As shown;

[0102] (2) Preparation of negative electrode slurry and negative electrode sheet;

[0103] (3) The material is sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle type high-voltage soft-pack lithium-ion battery, wherein a ceramic adhesive diaphragm is used for winding during the core assembly, and after the winding is completed, the core needs to be subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production, and the temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 2min, and the surface pressure is 5±0.5kgf / cm 2; The temperature of pressurized low temperature rapid cooling is 10±3℃, the time is 2min, and the surface pressure is 6±0.5kgf / cm 2 , the actual set pressure calculation formula is as follows: set pressure = core width * core height - surface pressure;

[0104] The preparation of the positive electrode slurry specifically includes the following steps:

[0105] (1-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the positive electrode slurry;

[0106] (1-2) Dry powder mixing: Add the raw materials in the order of main material five-series or six-series high-voltage ternary 50%, conductive agent 100%, PVDF 100% and remaining main materials, and stir for 30 minutes to obtain a mixed dry powder;

[0107] (1-3) mud-like stirring: adding 28% by weight of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture;

[0108] (1-4) High viscosity stirring: Add the obtained muddy mixture to the conductive slurry and stir evenly, then add the remaining NMP to adjust the viscosity. After the viscosity is adjusted to 9200 mPa.s, degassing is performed to obtain the positive electrode slurry. The specific stirring process is shown in Table 1;

[0109] The preparation of negative electrode slurry specifically includes the following steps:

[0110] (2-1) Weighing raw materials: weigh the raw materials according to the mass percentage of the negative electrode slurry;

[0111] (2-2) Preparation of glue solution: CMC and deionized water are added into a mixing barrel at a ratio of 1.4:98.6 and stirred. First, stir at a low speed for 5 minutes, change the speed after cleaning and stir for 10 minutes, clean again, and then stir at a high speed for 20 minutes. After the high-speed stirring, observe that the glue solution is transparent and clear, and there are no glue particles in the glue solution. If there are residual undissolved glue particles in the glue solution, the glue application time is extended by 30-60 minutes accordingly. After the glue solution is qualified, vacuum degassing is carried out for 10 minutes before discharging. The final glue solution viscosity is 2500mpa.s.

[0112] (2-3) Preparation of graphite pre-slurry: Graphite and 4 / 5 of the conductive agent are added to a slurry mixing barrel for dry powder stirring; then, 2 / 5 of the glue is added and stirred for a first soaking; then, 4 / 5 of the conductive slurry is added for a second soaking and stirring; finally, deionized water is added for viscosity adjustment, and the final viscosity is 6200 mPa.s. The specific stirring process is shown in Table 2;

[0113] (2-4) Preparation of silicon oxide pre-slurry: Add the silicon oxide and the remaining conductive agent into a slurry mixing barrel for dry powder stirring; then, add 1 / 12 of the glue solution and perform a first soaking stirring; then, add the remaining conductive slurry and perform a second soaking stirring; finally, add deionized water to adjust the viscosity, and the final viscosity is 6350mpa.s. The specific stirring process is shown in Table 3;

[0114] (2-5) Liquid fusion: Add graphite pre-slurry and silica pre-slurry into a mixing barrel for liquid dissolution stirring; then, add the remaining glue solution and stir for dilute glue; then adjust the slurry viscosity by adding deionized water, and the final viscosity is 2950mPa.s; then, add the suspending agent SBR to the slurry after the viscosity adjustment and stir for suspension; finally, add NMP to the slurry after stirring and reverse degassing to obtain qualified negative electrode slurry. The specific stirring process is shown in Table 4.

[0115] Comparative Example 1

[0116] During the preparation of the lithium-ion battery, the negative electrode slurry was prepared by a rapid slurry mixing method (as shown in Table 5), and the other conditions were the same as those in Example 1;

[0117] Table 5 Process parameters of rapid slurry mixing method

[0118]

[0119] Comparative Example 2

[0120] In the preparation process of lithium-ion batteries, the positive electrode sheet is prepared using a positive electrode sheet head tab structure (such as the attached Figure 2 As shown), the tabs are produced using conventional adhesive tape, and other conditions are the same as those in Example 1.

[0121] Comparative Example 3

[0122] During the preparation of lithium-ion batteries, no ceramic adhesive diaphragm was used for winding during the core assembly process, and the core was not subjected to pressurized and heated short-circuit testing and pressurized low-temperature rapid cooling and shaping after winding. Other conditions were the same as those in Example 1.

[0123] The batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries (5560100-5000mAh produced by Fengfan Co., Ltd.) were tested and compared, and the results are as follows:

[0124] Table 6 shows the high temperature short circuit test results of the batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries. It can be seen from the table that the batteries in Examples 1 and 2 prepared by the method of the present invention can meet the 55°C high temperature short circuit test, and the maximum temperature of the battery body during the high temperature short circuit process is relatively similar and lower than that of the batteries prepared in other schemes;

[0125] Table 6 High temperature short circuit test results of batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries

[0126]

[0127] like Figure 3 The discharge curve comparison diagram of the batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries shows that the discharge platforms of the batteries in Examples 1 and 2 prepared by the method of the present invention are similar and higher than the discharge platforms of the batteries in the other comparative examples;

[0128] like Figure 4 The cycle comparison curves of the batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries are shown in the figure. It can be seen from the figure that the cycle retention rates of the batteries in Examples 1 and 2 prepared by the method of the present invention are similar and are better than those of the batteries in the other comparative examples;

[0129] like Figure 5 The figure is a rate comparison curve of the batteries prepared in Examples 1-2 and Comparative Examples 1-3 and conventional batteries. It can be seen from the figure that the rate discharge performance of the batteries in Examples 1 and 2 prepared according to the method of the present invention is similar and is better than that of the batteries in the other comparative examples;

[0130] It can be concluded from the above that the method of the present invention can effectively improve the battery cycle performance, battery rate discharge performance, increase the battery discharge platform and improve battery safety, and expand the application range of lithium-ion batteries.

[0131] The various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to in detail.

[0132] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high-rate cycle high-voltage soft-pack lithium-ion battery, characterized in that: The soft-pack lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum-plastic film; Wherein, the positive electrode sheet comprises a positive electrode slurry and a positive electrode current collector; The negative electrode sheet comprises a negative electrode slurry and a positive electrode current collector; The diaphragm is a three-layer diaphragm including a PE base film, a ceramic coating and a ceramic adhesive coating; The electrolyte additive includes at least one of DTD, FEC and HTCN; The aluminum-plastic film is a heat-sealable aluminum-plastic film with a three-layer structure of nylon, aluminum and PP.

2. A high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 1, characterized in that: The solvent of the positive electrode slurry is NMP, the mass percentage of the solid material content of the positive electrode slurry is 65-70%, and the viscosity of the positive electrode slurry is 7500-9500 mpa.s; The solid material comprises the following raw materials in percentage by mass: 94-97% of five-series or six-series high-voltage ternary, 0.5-1.5% of conductive agent, 1.0-2.0% of conductive paste and 1.5-2.5% of binder; The positive electrode current collector is an aluminum foil with a thickness of 10-15 um.

3. A high-rate cycle high-voltage soft-pack lithium-ion battery according to claim 1, characterized in that: The solvent of the negative electrode slurry is water and NMP, the mass percentage of the solid material content of the negative electrode slurry is 40-50%, and the viscosity of the negative electrode slurry is 2000-4000 mpa.s; The solid material comprises the following raw materials in percentage by weight: 77-82% of graphite, 13.6-17.2% of silicon oxide, 0.8-1.2% of conductive agent, 0.05-0.1% of conductive paste, 1.35-1.5% of CMC and 2.2-3.0% of suspending agent; the amount of NMP added is 1-4% of the weight of the solid material; The negative electrode current collector is a copper foil with a thickness of 5-8 um.

4. A high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 1, characterized in that: The thickness of the diaphragm is 12-15um, wherein the thickness of the PE base film is 6-10um, the thickness of the ceramic coating is 1-4um, and the thickness of the ceramic glue coating is 1-3um; The mass percentage of the additive is 1.5%; The thickness of the aluminum-plastic film is 0.088-0.113 mm.

5. A method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to any one of claims 1 to 4, characterized in that: The specific steps include: (1) Preparation of positive electrode slurry and positive electrode sheet; (2) Preparation of negative electrode slurry and negative electrode sheet; (3) The materials are sequentially subjected to core assembly, liquid injection, activation, formation and capacity separation to obtain a high-rate cycle-type high-voltage soft-pack lithium-ion battery.

6. The method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 5, characterized in that: The preparation of the positive electrode slurry in step (1) specifically includes the following steps: (1-1) Weighing raw materials: weigh the raw materials of the positive electrode slurry according to the mass percentages described in claim 1 or 2; (1-2) Dry powder mixing: Add five-series or six-series high-voltage ternary, conductive agent and binder in sequence and stir to obtain mixed dry powder; (1-3) mud-like stirring: adding a portion of NMP to the mixed dry powder and mud-like stirring to obtain a mud-like mixture; (1-4) After adding the conductive slurry to the muddy mixture and stirring evenly, the remaining NMP is added to adjust the viscosity. After the viscosity is adjusted to 7500-9500 mPa.s, the positive electrode slurry is obtained by degassing.

7. The method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 5, characterized in that: The positive electrode sheet in step (1) is prepared by a method of having a positive electrode tab in the middle, and the tab is affixed with high temperature resistant masking tape.

8. The method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 5, characterized in that: The preparation of the negative electrode slurry in step (2) specifically includes the following steps: (2-1) Weighing raw materials: weighing raw materials for negative electrode slurry according to the mass percentages described in claim 1 or 3; (2-2) Preparation of glue solution: the CMC and the water are mixed and then glued to obtain glue solution, wherein the viscosity of the glue solution is 2000-4000 mPa.s; (2-3) Preparation of graphite pre-slurry: After dry powder mixing of the graphite and part of the conductive agent, adding part of the glue solution for primary infiltration and stirring; then adding part of the conductive slurry for secondary infiltration and stirring; finally, adding water for viscosity adjustment to 6000-6500 mPa.s to obtain graphite pre-slurry; (2-4) Preparation of silicon oxide pre-slurry: After dry powder mixing of the silicon oxide and the remaining conductive agent, a portion of the glue solution is added for primary wetting and stirring; then the remaining conductive paste is added for secondary wetting and stirring; finally, water is added for viscosity adjustment to 6000-6500 mPa.s to obtain silicon oxide pre-slurry; (2-5) Liquid fusion: The graphite pre-slurry and the silicon oxide pre-slurry are mixed and stirred for liquid dissolution. After completion, the remaining glue solution is added for dilute glue stirring, and then the water is added for viscosity adjustment to 2000-4000 mPa.s. Finally, the suspending agent is added in sequence for suspension stirring and NMP is added for inversion degassing to obtain the negative electrode slurry.

9. The method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 8, characterized in that: In step (2-3), the amount of the conductive agent added is 4 / 5-5 / 6 of the total amount, the amount of the glue added is 2 / 5-5 / 12 of the total amount, and the amount of the conductive paste added is 4 / 5-5 / 6 of the total amount; In step (2-4), the amount of the conductive agent added is 1 / 6-1 / 5 of the total amount, the amount of the glue added is 1 / 12-1 / 10 of the total amount, and the amount of the conductive paste added is 1 / 6-1 / 5 of the total amount.

10. The method for preparing a high-rate cycle-type high-voltage soft-pack lithium-ion battery according to claim 5, characterized in that: The winding core assembly in step (3) is wound using a ceramic rubber diaphragm, and after the winding is completed, the winding core is subjected to a pressurized and heated short-circuit test and a pressurized low-temperature rapid cooling and shaping production; The specific parameters of the pressurized and heated short-circuit test and the pressurized low-temperature rapid cooling shaping production are as follows: The temperature of the pressurized and heated short-circuit test is 85±3°C, the time is 1-2 minutes, and the surface pressure is 5±0.5kgf / cm 2 ; The temperature of the pressurized low-temperature rapid cooling setting is 10±3°C, the time is 1-2min, and the surface pressure is 6±0.5kgf / cm 2 .